Surgical endoscopic management of sinonasal diseases in Kinshasa, Democratic Republic of the Congo - NTUMBA MALEMBA, Alain; Mpiana Junior, Sympho; Tshingamb Kamin, Yasmin; NGIMBI NTUMBA , Elisabeth; Kayembe Kabutakapua, Emile; Kalala Kabala, Hilaire; KEMBIA TSHIKOLU , Elisée; MPANZU KIASI , Claudine; TSHIMBADI NKONGOLO , Augustin; LEVIE , Patrick; Nyembue Tshipukane, Dieudonné (Orapuh Journal, 2025)
Introduction Endoscopic sinus surgery (ESS) is considered the gold standard for the surgical management of sinonasal diseases but remains relatively less well known in our region. Purpose The aim of this study was to identify the indications for ESS and examine the sociodemographic, clinical, and satisfaction characteristics of patients undergoing the procedure. Methods A descriptive case series study was conducted from 2021 to 2024, enrolling patients who underwent ESS in three hospitals in Kinshasa. Sociodemographic characteristics, surgical indications, procedures, clinical outcomes, and patient satisfaction—measured using a symptom severity visual analogue scale—were evaluated. Allergy prick tests, preoperative endoscopy, and sinus CT scan findings were recorded. The Pearson chi-square (χ²) test and Student’s t-test were used for data comparison, with statistical significance set at p < 0.05. Patients were followed up on postoperative days 1, 7, 15, and 30. Results A total of 68 patients underwent surgery, with a mean age of 43.6 ± 19.8 years, and 58.8% were male. Nasal obstruction was the most frequently reported symptom (77.9%), followed by rhinorrhea (54.4%) and dysosmia (45.6%). Allergy and asthma were present in 22.0% and 11.8% of patients, respectively. Chronic rhinosinusitis with nasal polyps (CRSwNP) was the most common surgical indication (36.8%), followed by chronic rhinosinusitis without nasal polyps (CRSsNP) and sinonasal tumors, each accounting for 22.1%. Middle meatotomy (MM) was the most frequently performed surgical procedure (50.0%), followed by endonasal polypectomy (45.6%), anterior ethmoidectomy (35.3%), and inferior turbinate cauterization (28.7%). Histological analysis revealed that 63.2% of inflamed polyps were eosinophilic. Approximately one in four patients experienced minor complications, including epistaxis (13.2%), headache (8.8%), and palpebral edema (1.5%). By the 30th postoperative day, all symptoms had significantly improved, except for epistaxis. Conclusion This study demonstrated that CRSwNP was the most common indication for ESS, with MM being the most frequently performed surgical procedure. Patient satisfaction was high, suggesting that ESS should be further implemented for the management of sinonasal diseases in our setting.